Reductive model of the conscious mind - Galus, Wieslaw 1947-; Starzyk, Janusz 1947- (A volume in the Advances in human and social aspects of technology (AHSAT) book series, 2021)
"This book focuses on phenomenon of consciousness in attempt to explain it on materialistic basis. It looks at consciousness from three different perspectives: a philosophical (theoretical), biological, and machine view of the brain and mind" - Provided by publisher